Knowing in the Bones - Eva Pomeroy; Arawana Hayashi; Sebastian Jung; Beth Mount; Asiya Odugleh-Kolev; Otto Scharmer; Ericka Toledo-Zurita; Joost van der Cruijsen (Journal of Awareness-Based Systems Change)
While “seeing the system” is a common frame in systems change work, and one around which a multitude of methods have been developed, sensing the system hints at something beyond the cognitive engagement that often form the basis of these methods. Sensing calls on us to draw on epistemologies less prevalent in systems change discourse, including embodied, aesthetic and intuitive forms of knowing, to source our system inquiry from a more holistic and complete understanding of what it is to be that system. The 4D Mapping practice from Social Presencing Theater (SPT) offers a methodology to do this. It is a practice that integrates systems mapping and embodiment to see, sense and make sense of system dynamic. In this dialogue, four leaders who have integrated 4D Mapping in their broader systems change initiatives come together to dialogue with members of the SPT team. They share and reflect on their experiences of mapping their systems, the role and impact of the experience within their initiative, and the lasting effect on themselves as leaders.